A Novel Synthesis of Thioesters by Palladium-Catalyzed Carbonylative Coupling Reactions of Amides with Disulfides - Zhao, Yu; Xiao, Yongmei; Mai, Wenpeng; Zhang, Wanru; Yuan, Jinwei; Yang, Liangru (Synthesis, 2025)
A novel and simple catalytic protocol for the synthesis of thioesters from pyridinamides and disulfides has been developed, where pyridinamide was used as a cheap, efficient and relatively safe carbonyl source. Diverse substituted pyridinamides are capable of coupling with diaryl disulfides via N–C/S–S cleavage to produce the desirable thioesters in moderate to good yields. This procedure employs convenient conditions and accommodates a wide range of amide substrates, offering a straightforward and novel pathway to prepare various thioesters without the use of toxic thiols or carbon monoxide gas, while also avoiding the need for costly solid carbon monoxide alternatives. Furthermore, the utilization of pyridinamide as a carbonyl source offers a valuable enhancement for the synthesis of thioesters from amides, which have been relatively rare until now.
Keywords: palladium; thioester; amide; C–N cleavage; C–S bond